Kepatuhan Produk Cicil Emas terhadap Fatwa DSN-MUI No. 77/2010 dan Penerapannya di Bank Syariah Indonesia serta Lembaga Keuangan Syariah Lainnya: A Systematic Literature Review (SLR) - hurul aini asofa marwah (Journal of Fiqh in Contemporary Financial Transactions, 2026)
AbstractGold installment products are an innovation in Islamic financial institutions that combine financing and investment based on Sharia principles. This study aims to examine the implementation of gold installment products through the murabahah contract and their compliance with DSN-MUI Fatwa No. 77/DSN-MUI/VI/2010. This research employs a Systematic Literature Review (SLR) by analyzing 14 relevant articles published in national journals. The findings indicate that gold installment products are generally implemented in accordance with Sharia principles, with transparent pricing and agreed profit margins. Some institutions apply a combination of murabahah and rahn contracts, which is permissible if conducted separately. Gold installment products enhance access to gold investment and promote Islamic financial inclusion, although challenges remain in customer understanding and product education.Keywords: gold installment, murabahah, DSN-MUI fatwa, systematic literature review, Islamic finance.